Typology Conflict of Forest Area on Boundary Demarcation Process in Bangka Island Region - Nilasari, Afrisna; Murtilaksono, Kukuh; Soetarto, Endriatmo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTDesignation of forest area in Bangka Island region, Bangka Belitung Province according to Kepmenhut 357/Menhut-II/2004 has provoked a conflict between the various interested parties. Boundary demarcation process as the next stage from designation forest area had a conflict with local communities. This study had purpose to identifylanduse and landcover condition of forest area and the type of conflict. The applied methode was image intepretation and classification and alsoRaTA (Rapid Land Tenure Asessment). The study showed that landuse and landcover condition was dominated with grassland and the form of occupied local people is cropland, palm oil plantation, open field, and the settlement. Tke kind of conflict in the field study was strugle of access and withdrawall rights of land resources in the forest area that causes by different persepsion between local peoples and the Goverment as the parties has management and demarcation boundary authorithy of forest area with the problem is illegal activity and land convertion from other use area into forest area. Forest Management based by The Community would be ideal conflict resolution and those need the socialisation, intensive and effective communication between the parties that had a conflict.Keywords: forest land tenure conflict, landuse and landcover, conflict resolutionABSTRAKPenunjukan kawasan hutan di wilayah Pulau Bangka Provinsi Kepulauan Bangka Belitung berdasarkan Keputusan Menteri Kehutanan Nomor 357/Menhut-II/2004 menimbulkan konflik bagi para pihak yang berkepentingan. Proses penataan batas sebagai tahapan berikutnya dari penunjukan kawasan hutan mengalami penolakan dan konflik dengan masyarakat lokal. Penelitian ini memiliki tujuan untuk mengetahui kondisi penutupan dan penggunaan lahan kawasan hutan serta tipe konflik yang terjadi melalui intepretasi dan klasifikasi citra satelit serta analisis RaTA (Rapid Land Tenure Asessment). Hasil penelitian menunjukkan bahwa kondisi penutupan lahan wilayah penelitian didominasi oleh semak belukar dan bentuk okupasi lahan masyarakat berupa lahan terbuka, kebun sawit, kebun campuran dan pemukiman. Tipologi konflik yang terjadi lebih kepada konflik perebutan hak akses dan hak pengelolaan sumber daya lahan yang terdapat di dalam kawasan hutan yang disebabkan karena perbedaan persepsi antara masyarakat dengan Pemerintah sebagai pemegang wewenang pengelolaan dan penataan batas kawasan hutan dengan bentuk permasalahan berupa perambahan kawasan hutan dan adanya alih fungsi lahan dari Areal Penggunaan Lain (APL) menjadi kawasan hutan. Program Pengelolaan Hutan Berbasis Masyarakat (PHBM) menjadi resolusi konflik yang ideal dan perlu dilakukan sosialisasi dan komunikasi yang intensif dan efektif antar para pihak.Kata kunci: konflik penguasaan lahan, penutupan dan penggunaan lahan, resolusi konflik